THE EFFECT OF SUBJECTIVE ANALYSIS ON THE QUALITY OF RED SNAPPER BONE MEAL (LUTJANUS SP) - Nurainy kaliky (Yayasan Education and Social Center, 2022)
Fishbones are fishery waste that can be processed and utilized into economic value products, namely fishbone meals. One fish whose bones can be used as a fishbone meal is the red snapper (Lutjanus sp). As the primary raw material for making fishbone meals, the bones of red snapper (Lutjanus sp) are rich in calcium mineral salts such as calcium phosphate and phosphorus. Calcium is a mineral that is needed by the human body. Calcium is perfect for babies, children, pregnant women, and the elderly. Calcium deficiency can cause osteoporosis. This study aims to utilize fish bone waste to have economic value and provide information to the public about fishbone meals rich in calcium minerals. This study used an experimental method with two replications. The results showed an increase in the color, texture, and odor of bone meal of red snapper (Lutjanus sp). While the Diversity Analysis (ANOVA) test showed no significant effect on each parameter